US7 score in the subacute phase does not correlate with outcomes in Chikungunya arthritis - Benzeeta Pinto; Anu Mohan Desai; Farha Furruqh; K N Sangeeta; B Sheba Charles; John Michael Raj; Ramya Janardana; Vineeta Shobha (Indian Journal of Rheumatology)
Introduction: Chikungunya fever is a remerging disease and may lead to postchikungunya inflammatory joint pain. Objective: To study the clinical and ultrasound (US) features of chikungunya arthritis in the subacute phase and to determine if high disease activity on US on is associated with chronic disability. Materials and Methods: We conducted a prospective observational study of all patients who presented with subacute chikungunya arthritis over 1 year duration. Chikungunya fever was diagnosed by consistent clinical picture with specific immunoglobulin M positivity. Disease activity assessments and US-7 score were performed at baseline. Indian Health Assessment Questionnaire (HAQ) and pain on numerical rating scale were done at baseline and 1 year of follow-up. Results: We included 23 patients (18 females) with a median age of 43 years. Most (22/23) patients had polyarticular disease with negative rheumatoid factor and anticyclic citrullinated peptide. Ultrasound revealed synovitis in all and tenosynovitis in most patients. The median (interquartile range) US7 score, Disease Activity Score 28 erythrocyte sedimentation rate (DAS28-ESR) score, Indian HAQ, and pain at presentation were 15 (11), 4.4 (2), 0.92 (0.7), and 5 (6), respectively. Twenty patients were treated with a short course of glucocorticoids. One-year follow-up was available in 20 patients. The median HAQ and pain score at follow-up were 0.08 (0.21) and 1 (1), respectively . No correlation was found between US7 score, DAS28, swollen joint count, tender joint count, ESR, HAQ score, or pain at presentation with HAQ and pain at follow-up. Conclusion: Disease activity at presentation as assessed by US7 score did not correlate with disability and pain at 1 year of follow-up in patients with chikungunya arthritis.